2021
DOI: 10.1099/ijsem.0.004888
|View full text |Cite
|
Sign up to set email alerts
|

‘Candidatus Xiphinematincola pachtaicus' gen. nov., sp. nov., an endosymbiotic bacterium associated with nematode species of the genus Xiphinema (Nematoda, Longidoridae)

Abstract: An intracellular bacterium, strain IAST, was observed to infect several species of the plant-parasitic nematode genus Xiphinema (Xiphinema astaregiense, Xiphinema incertum, Xiphinema madeirense, Xiphinema pachtaicum, Xiphinema parapachydermum and Xiphinema vallense). The bacterium could not be recovered on axenic medium. The 16S rRNA gene sequence of IAST was found to be new, being related to the family Burkholderiaceae, class Betaproteobacteria. Fungal endosymbionts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…Microbes could play significant roles in the biology of plant-parasitic nematodes (PPNs), which cause up to 25% of global crop yield loss and cost ∼$100 billion annually ( Nicol et al, 2011 ). Recent findings suggest PPNs can harbor mutualist symbionts, like Xiphinematobacter (Verrucomicrobia) ( Vandekerckhove et al, 2000 ; Brown et al, 2015 ) and Xiphinematincola (Burkholderiales) ( Palomares-Rius et al, 2016 , 2021 ), or symbionts with unknown phenotypes, including Cardinium (Bacteroidetes) ( Noel and Atibalentja, 2006 ; Brown et al, 2018 ) and Wolbachia (Alphaproteobacteria) ( Haegeman et al, 2009 ; Brown et al, 2016 ), but current studies on the diversity and roles of such microbes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes could play significant roles in the biology of plant-parasitic nematodes (PPNs), which cause up to 25% of global crop yield loss and cost ∼$100 billion annually ( Nicol et al, 2011 ). Recent findings suggest PPNs can harbor mutualist symbionts, like Xiphinematobacter (Verrucomicrobia) ( Vandekerckhove et al, 2000 ; Brown et al, 2015 ) and Xiphinematincola (Burkholderiales) ( Palomares-Rius et al, 2016 , 2021 ), or symbionts with unknown phenotypes, including Cardinium (Bacteroidetes) ( Noel and Atibalentja, 2006 ; Brown et al, 2018 ) and Wolbachia (Alphaproteobacteria) ( Haegeman et al, 2009 ; Brown et al, 2016 ), but current studies on the diversity and roles of such microbes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…We also noted a decrease in the abundance of Nematoda in eukaryotes identi ed in aplastic anaemia patients and a decrease in the abundances of Enoplea, Trichinellida, Trichuridae, Enterocytozoon and Trichuris within this phylum, which were negatively correlated with the contents of eicosenoate, docosatetraenoate and 10-transsheptadecenoate in the plasma. In addition, the number of Mycoavidus species 37 in the nematode-related bacterial community was decreased and negatively correlated with docosadienoate and docosatetraenoate. Previous studies have shown that nematodes are primarily associated with unsaturated fatty acids, consistent with our ndings.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Cardinium has already recovered from root lesion nematode P. penetrans (Denver et al , 2016) and cyst nematodes belonging to genera Globodera and Heterodera (Shepherd et al , 1973; Endo, 1979; Walsh et al , 1983a, b; Yang et al , 2017). Other endosymbiont bacteria reported from nematodes belong to the genera Xiphinematincola pachtaicus , Wolbachia and Xiphinematobacter (Haegeman et al , 2009; Palomares-Rius et al , 2014, 2021). During the present study, the endosymbiosis of a Cardinium sp.…”
Section: Discussionmentioning
confidence: 99%